Laser patterning of boron carbon nitride electrodes for flexible micro-supercapacitor with remarkable electrochemical stability/capacity - Karbhal, Indrapal; Basu, Aniruddha; Patrike, Apurva; Shelke, Manjusha V. (Carbon, 2021)
High performance, all solid-state planar micro-supercapacitor (MSC) with interdigitated Boron carbon Nitride (BCN) electrodes are fabricated via fast, scalable laser patterning technique. Heteroatom doping desirably enhances the electrochemical activity of carbon electrodes. This BCN based micro-supercapacitor showed comparatively very high specific capacitance of 72 mFcm(-2) at a current density of 0.15 mAcm(-2). Even at a high current density of 1 mAcm(-2) device showed specific capacitance as high as 17 mFcm(-2). It has demonstrated excellent electrochemical stability when tested up to 80000 cycles without any sign of further decay in capacity/efficiency. This device showed stable capacity even after bending at 150 degrees angle, for 1500 times during cycling showing remarkable flexibility. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: BCN; Co-doping; Energy storage; Flexible; Laser patterning; Micro-supercapacitor